Policing and the Clash of Masculinities - McGinley, Ann (2015)
In 2014 and 2015, the news media inundated U.S. society with reports of brutal killings by police of black men in major American cities. Unfortunately, police departments do not typically keep data on police killings of civilians. The data that exist do show, however, that at least for a five-month period in 2015, there was a disproportionate rate of police killings of unarmed black men. There is no question that race and class play a key role in the nature of policing that occurs in poor black urban neighborhoods, but the relationship between police officers and their victims is not only about race and class. It is also about gender. Black men, especially those living in poor neighborhoods, are the common victims of police scrutiny, stop and frisks, arrests, incarcerations, and killings. White men are almost invariably the police personnel who kill unarmed black males in the streets. Performances of masculinity by the police and their victims exacerbate this problem. This article uses multidimensional masculinities theory to analyze the intersection of race, gender, and class at which this problem occurs. It evaluates the crucial role gender plays in the formation, education, training, and work behavior of police officers. It also discusses how black civilian men’s performances of masculinity may play a role in their treatment by police officers, and when combined with the police officer’s performance of masculinity, may turn deadly. The article concludes that an understanding of masculinities studies should lead to important policy changes in the gathering of evidence, research, education and training of police, and to a reassessment by all communities in the United States of what exactly makes men masculine. These understandings, combined with policy changes, may help prevent further police violence perpetrated on innocent victims